Magnetically mediated thermoacoustic imaging toward deeper penetration - Feng, Xiaohua (2013)
Magnetically mediated thermo-acoustic effect is predicted in theory and demonstrated in phantom studies in this letter. By applying transient current to a compact magnetically resonant coil at radio frequency below 20 MHz, large electric field is inducted by magnetic field inside conductive objects which then undergoes joule heating and emanates acoustic signal thermo-elastically. The magnetic mediation approach with low radio frequency can provide deeper penetration into conductive objects which may extend thermoacoustic imaging to deep laid human organs. Both incoherent time domain and coherent frequency domain approaches are discussed with the latter demonstrated potential for portable imaging system.